2018
DOI: 10.1039/c8ra00744f
|View full text |Cite
|
Sign up to set email alerts
|

Differential CRABP-II and FABP5 expression patterns and implications for medulloblastoma retinoic acid sensitivity

Abstract: This study demonstrates the highly variable expression patterns of CRABP-II and FABP5 in medulloblastoma cells and their correlation with RA sensitivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…Secondly, there were increased levels of CRAPB2 and FABP5, retinoid binding proteins essential for carrying the RA to their nuclear receptors. In medulloblastoma, it has been shown that the levels of these retinoid binding proteins can lead to either proliferation when FABP5 levels are above CRABP2 levels as shown in our study or to growth inhibition (when CRAPB2 > FABP5) 23 , 24 . While both proteins were upregulated by the retinoids, FABP5 was found to be at higher increased levels than CRABP2, suggesting an increased proliferation.…”
Section: Discussionsupporting
confidence: 60%
“…Secondly, there were increased levels of CRAPB2 and FABP5, retinoid binding proteins essential for carrying the RA to their nuclear receptors. In medulloblastoma, it has been shown that the levels of these retinoid binding proteins can lead to either proliferation when FABP5 levels are above CRABP2 levels as shown in our study or to growth inhibition (when CRAPB2 > FABP5) 23 , 24 . While both proteins were upregulated by the retinoids, FABP5 was found to be at higher increased levels than CRABP2, suggesting an increased proliferation.…”
Section: Discussionsupporting
confidence: 60%
“…Secondly, there were increased levels of CRAPB2 and FABP5, retinoid binding proteins essential for carrying the retinoids to their nuclear receptors. In medulloblastoma, it has been shown that the levels of these retinoid binding proteins can lead to either proliferation when FABP5 levels are above CRABP2 levels as shown in our study or to growth inhibition (where CRAPB2>FABP5) [3,33] . While both proteins were upregulated by the retinoids, FABP5 was found to be at higher increased levels than CRABP2, suggesting an increased proliferation.…”
Section: Discussionsupporting
confidence: 59%
“…In our study, it was upregulated in sPV compared to mPV, which agrees with previous work showing higher serum levels of psoriasin in patients with severe psoriasis 9 and a reduction after treatment with biological agents 15 . KRT6A is one of the stress keratins that regulate keratinocyte differentiation and correlation to proteins that participate in EGFR and retinoic acid signalling 22,23 . Our results demonstrated that it was upregulated in DIA but downregulated in the PRM test, which the conclusions of the previous study can explain that individual stress keratin genes are associated with partially distinct gene networks 24 .…”
Section: Discussionmentioning
confidence: 99%